DETERMINAN NILAI PERUSAHAAN KONSUMEN NON-SIKLUS DI BURSA EFEK INDONESIA - Nuridin; Rosdiana (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2024)
This research was conducted to determine the influence of the current ratio, return on equity and debt to equity ratio on company value in non-cyclical consumer companies listed on the Indonesia Stock Exchange. This research method is quantitative analysis. The data used is secondary data from non-cyclical consumer companies listed on the Indonesian Stock Exchange. Analysis method using multiple and simple linear regression. The results of this research show that together the current ratio, return on equity and debt to equity ratio have a significant influence on company value. Partially, the current ratio and return on equity have a positive and significant effect on company value, while the debt to equity ratio has a negative and significant effect on company value